2017
DOI: 10.3390/su9101739
|View full text |Cite
|
Sign up to set email alerts
|

Freedom of Mass Communication in the Digital Age in the Case of the Internet: “Freedom House” and the USA Example

Abstract: Similar to various other disciplines, there have been significant changes and developments in the communication domain during the first quarter of the 21st century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
(4 reference statements)
0
5
0
2
Order By: Relevance
“…The governance theory of “data freedom theory” is often placed in the context of economic or political unilateralism. The development of the digital economy is based on the free flow of data and the value of efficiency [ 22 ]. Suppose strong data localization regulations are made based on traditional sovereignty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The governance theory of “data freedom theory” is often placed in the context of economic or political unilateralism. The development of the digital economy is based on the free flow of data and the value of efficiency [ 22 ]. Suppose strong data localization regulations are made based on traditional sovereignty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this framework, Internet journalism has been launched (digital newspapers and blog sites), and sites such as YouTube have been established to watch and broadcast videos. Development is not limited to these examples: social networking sites such as Facebook and Twitter were also established shortly and it was observed that there was a large increase in the number of users (Avşar & Öngören, 2010, p. 13; Dolunay et al, 2017, p. 10).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Information technologies and informatization of society are considered as key factors in the establishment of the global information and communication environment [18], e-commerce, and the digital economy, as well as accelerating the globalization [15], [19], [20]. It is suggested that the establishment of the information society allows to raise the status and competitiveness of the country [21]- [23] and has a positive effect on the socioeconomic situation of its population amid globalization [24]- [26].…”
Section: Literature Reviewmentioning
confidence: 99%